PENGARUH TEKNIK BERBALAS PANTUN UNTUK MENINGKATKAN KOMUNIKASI INTERPERSONAL SISWA MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 9 PEKANBARU - Fani, Dwi Novita; Saam, Zulfan; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract :This study aims to determine the differences in the level ofinterpersonal communication before and after given the pantun reciprocated techniquethrough group guidance, and to know the effect of the pantun reciprocated technique toimprove student interpersonal communication through group guidance. The study wasconducted at Pekanbaru State Middle 9 of 7 subjects with purposive samplingtechnique. The research design was pre-experiment with the one group pre-test post-testmodel. The instrument of data collection used is an instrument consisting of indicatorsof interpersonal communication. The results showed that there were differences in thelevel of interpersonal communication of students before and after given the pantunreciprocated technique through group guidance with a significance value of 0.017<0.05. Interpersonal communication of 7 students who were previously in the lowcategory experienced an increase after being given the pantun reciprocated techniquethrough group guidance which were mostly in the high category. by 60% while 40% isinfluenced by other factors that come from within students and the environment.Key Words: Pantun Reciprocated Technique, Interpersonal Communication, Group Guidance.